2017
DOI: 10.18203/2320-6012.ijrms20173097
|View full text |Cite
|
Sign up to set email alerts
|

Association of subclinical hypothyroidism and HbA1c levels in non-diabetic subjects attending rural tertiary care centre in central India

Abstract: NTRODUCTIONThyroid disorders are very common in the general population and is second most common condition affecting the endocrine system after diabetes mellitus. Decreased production of thyroid hormone is the key feature of hypothyroidism.2 Subclinical hypothyroidism is defined as an elevated serum TSH level and normal concentrations of free T3 (FT3), free T4 (FT4), T3 and T4.1 It is often complicated by conditions such as dilutional hyponatremia, anaemia and hyperlipidemia. Subclinical hypothyroidism is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The Male : Female sex ratio was 2.33 and 3.44 was comparable to each other (X 2 =0.24, df=1,p>0.05) The parameters were significantly higher like; FPG (mg/dl)-91.56±7.89 and 80.92±5.82 (t=7.28,df=88,p<0.0001); HbA1C-7.12± 3.45 and 5.34± 2.91 (t=9.83,df=88,p<0.0001); Fructosamine (μmol/L)-593.87±56.89 and 257.92±8.95 (t=5.73,df=88,p<0.001) in Hypothyroid group as compared to Euthyroid group respectively. These findings are similar to Ram VS et al 26 et al they found that there was a positive correlation between the levels of serum TSH (µU/L) and HbA1c (%) in all the participants of the study by Pearson's correlation coefficient (r=0.35, p < 0.0001). Also Sridevi V. Udup 27 they found that The fructosamine levels were significantly higher in Hypothyroid as compared to euthyroid group (p<0.05),…”
Section: Discussionsupporting
confidence: 90%
“…The Male : Female sex ratio was 2.33 and 3.44 was comparable to each other (X 2 =0.24, df=1,p>0.05) The parameters were significantly higher like; FPG (mg/dl)-91.56±7.89 and 80.92±5.82 (t=7.28,df=88,p<0.0001); HbA1C-7.12± 3.45 and 5.34± 2.91 (t=9.83,df=88,p<0.0001); Fructosamine (μmol/L)-593.87±56.89 and 257.92±8.95 (t=5.73,df=88,p<0.001) in Hypothyroid group as compared to Euthyroid group respectively. These findings are similar to Ram VS et al 26 et al they found that there was a positive correlation between the levels of serum TSH (µU/L) and HbA1c (%) in all the participants of the study by Pearson's correlation coefficient (r=0.35, p < 0.0001). Also Sridevi V. Udup 27 they found that The fructosamine levels were significantly higher in Hypothyroid as compared to euthyroid group (p<0.05),…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with other studies which had also reported similar results. 9,[12][13][14][15][16] We had excluded those with anaemia and no significant difference was found in haemoglobin levels in both groups. Some studies have found reduced erythropoiesis/ anaemia to be related to elevated HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…7 There are some studies that have brought out the relationship between elevated HbA1c levels and subclinical hypothyroidism in non-diabetic individuals. [8][9][10] Increase in HbA1c levels in non-diabetic subjects was also related to the coexistence of anaemia in hypothyroid patients. 11 In our study, we have attempted to assess the HbA1c levels among non-diabetic participants and determine its association with subclinical hypothyroidism, in a small south Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association (ADA) included HbA1c alone as a diagnostic tool for diabetes in 2010 [1], and we still consider HbA1c a reliable marker for diabetes control as per the 2018 ADA guidelines [8]. Factors altering HbA1c concentrations are Hb variants [9], hemolytic anemia, renal failure [10], hypothyroid [11], alcoholism, and hyperbilirubinemia. In this study, we aimed to look for HbA1c variations in nutritional anemia and their consideration with HbA1c as a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%